A Cross-Sectional Study on Aetiology, Clinical Profile and Management of Acute Pancreatitis over a period of Six months’ in a Tertiary Medical Care Hospital, YSR Kadapa - Babu, K. Leela Prasad; Kumar, S. Nelson; Rajaram, C.; Kareemulla, Shaik; Tejaswini, E.; Iram, Shaik Rahila; Reddy, S. Sai Prakash; Sindusha, D. (Indian Journal of Pharmacy Practice)
Background: An inflammation of the pancreas that lasts only a short time is called Acute Pancreatitis (AP). High levels of pancreatic enzymes in the blood and significant upper abdominal pain are its defining characteristics. Acute pancreatitis is typically a benign, self-limiting condition that cures itself without any problems. Objectives: The current study’s objective was to assess the prevalence of various AP etiologies, compare the variations in clinical characteristics among patients with various AP causes, assess the length of hospital stay, review the diagnostic techniques used to confirm AP, and monitor the clinical management of AP. Materials and Methods: A six-month prospective observational research study in a multifunctional tertiary hospital with 750 beds. The statistical analysis and evaluation of the acute pancreatitis clinical profile were done using SPSS (Statistical Package for Social Sciences). Results: The study included 50 patients in total. Males outnumbered females 96% to 4%, with a mean age of 34.7. Alcoholism accounted for the majority of the subjects’ 44 (88%). Abdominal pain was the most common symptom, reported by all 50 (100%) of them, followed by nausea and vomiting in 38 (76%), The majority of them were prescribed Ceftriaxone, which was given to 22 (44%) of them, followed by 13 (26%) prescriptions for Metronidazole, 10 (20%) for Meropenem, 6 (12%) for Cef-Sulbactam, and 4 (8%) for Ciprofloxacin. Pancreoflat was prescribed for 33 (66%). Proton-pump inhibitors were administered to 50 (100%) patients, followed by antacids in 22 (44%) cases, and histamine type 2 receptor blockers in 1 (2%) cases. 48 (96%) of them spent between 1 and 10 days in the hospital, 1 (2%) between 11 and 20 days, and 1 (2%) between 21 and 30 days. Conclusion: The study’s findings suggest that untreated acute pancreatitis can result in major side effects. Multicenter research involving a significant patient sample and the longer time durations is also recommended.
Keywords: Acute Pancreatitis; Alcohol; Abdomen Pain; Ceftriaxone; Pancreoflat; Hospital stay